The prevalence of mental retardation by gender, age, and age of diagnosis at Nobel Medical College, Biratnagar - Koirala, Naba Raj; Das, Ajoy Kumar; Bhagat, Santosh Kumar (Journal of Nobel Medical College, 2012)
Objectives: To evaluate the prevalence of mental retardation by gender and age of diagnosis at Nobel Medical College, Biratnagar. Methods: The data of all mentally retarded children recorded within a period of one year from 01st May 2011 to 30th April 2012 is analyzed retrospectively. Age, gender, IQ scores, the age of diagnosis, and their living place were evaluated. Results and conclusion: A total number 103 children attended the Psychiatric Out-patient Department of Nobel medical College and Teaching Hospital over the study period of one year. Out of all those 103 children, 67 children were with normal IQ scores, 7 with coexistence of epilepsy and other medical problems, and 3 children with incomplete case records, thus they were excluded from the study, and the subjects for further study was constituted by just 26 cases, who fulfilled the diagnostic criteria for Mental Retardation according to ICD-10. The overall prevalence of mental retardation in our study was 25% and the distribution of mental retardation amongst all those 26 cases were as follows: 2 cases (8%) were profound, 3 severe (12%), 7 (27%) were moderate and 9 (35%) mild, and 5 (19%) were borderline. Out of all those 26 mentally retarded children 11 were male (42%) and 15 (58%) were female, and of these cases, 07 were living in urban, and 19 in rural areas. Most of our cases were diagnosed between 6-10 years of age. DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7304 Journal of Nobel Medical College (2012), Vol.1 No.2 p.77-81